THE ALLIANCE TRACHYNION DISTACHYAE RIVAS-MARTINEZ 1978 IN CENTRAL ITALYIN CENTRAL ITALY - FANELLI, G.; BIANCO, P.M.; DE SANCTIS, M.; SERAFINI SAULI, A. (Annali di Botanica, 2010)
The therophytic basiphilous vegetation of Central Italy has been generally framed in a single association Trifolio scabri- Hypochoeridetum achyrophori Biondi et al. 1997. We show that a considerable floristic variation exists inside Trifolio-Hypochoeridetum in Central Italy, and that it should be treated as a complex of no less than five different associations: Medicagini rigidulae-Trifolietum scabri Fanelli et al. hoc loco, Trifolio scabri-Hypochoeridetum achyrophori Biondi, Izco. Ballelli & Formica 1997 s.s, Hippocrepido siliquosae- Brachypodietum distachyi Fanelli et al. ad interim, Trigonello gladiatae-Brachypodietum distachyi Fanelli et al. hoc loc, Crucianello latifoliae-Hypochoeridetum achyrophori Filesi, Blasi, Di Marzio 1996. These associations are floristically and ecologically distinct, and show different geographical ranges in Central Italy. The great diversity of Trachynion distachyae in Central Italy is related to the widespread occurrence of limestone and calcareous alluvial rocks and to a climate with abundant winter and autumn rains very favourable to the development of winter annuals.